Analisis Struktur, Perilaku, dan Kinerja Pasar Cabai di Desa Bayung Gede, Kecamatan Kintamani, Kabupaten Bangli - AGNELLIA, MADE AYU DESSY DORA; USTRIYANA, I NYOMAN GEDE; DJELANTIK, A.A.A. WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
AbstractAnalysis of Structure, Conduct, and Market Performance chili in Bayung Gede Village, Kintamani District, Bangli Regency.The research was done in Bayung Gede Village, Kintamani District, Bangli Regency. The study aims to determine the structure, conduct, and market performance. Data used is the qualitative and quantitative data. The results showed there are three types of marketing channels. Total of marketing agencies consisting of one person collector traders at once merchants inter-city and inter-island traders, and two retailers. Duopoly market structure shaped. Pricing is determined by the standard operational procedures (SOP) prices based on farmer’s recommendation. Market performance is measured by the analysis of marketing margin, the farmer's share, and marketing efficiency. At the first marketing channel marketing margin is IDR 3,000 with the farmer's share of 86.96% and 3.38% marketing efficiency, the second marketing channel marketing margin is IDR 5,000 with the farmer's share of 80% and 7.15% marketing efficiency, the third marketing channel marketing margin is IDR 15,000 with the farmer's share of 57.14% and 8.32% marketing efficiency. Farmers should strengthen institutions to strengthens the bargaining position.Keywords: structure, conduct, market performance, chili